CASE REPORTSEchocardiographic diagnosis of a massive left ventricular pseudoaneurysm: a case report - Sokolskaya, Nadezhda; Kopylova, Natalya; Slivneva, Inessa; Kolesnikov, Yan; Alshibaya, Michail; Zakharkina, Mariya (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Left ventricular aneurysm is one of the most troublesome complications of myocardial infarction. This complication results from LV wall rupture and presents as a cavity contained by pericardium and fragments of the ruptured wall. The risk of pseudoaneurysm rupture is very high and this makes the prognosis for the disease extremely unfavorable. A surgical correction, involving a patch repair of the LV wall, seems to be the only treatment modality. Echocardiography makes it possible to diagnose pseudoaneurysm of the left ventricle in most cases, while intraoperative transesophageal echocardiography is required for the in-process monitoring of intracardiac hemodynamics and assessment of intervention efficiency.